A form and process response study of a terminal ice cored ablation moraine. - Ross, A. Blair. (University of Ottawa (Canada), 1976)
The initiation and distribution of certain types of degradational processes together with resultant topographical changes on an ice cored moraine were studied in terms of the variation in micro climatic and glacial surge inputs operating on it. The study was conceived in terms of a process-response model. The study area was located on a large arcuate shaped ice cored end moraine, which rims the terminus of the Donjek Valley Glacier located in the Donjek Valley, St. Elias Mountains, Yukon Territory. The end moraine lies approximately 0.8 to 2.7 Km downvalley from the present position of the glacier and is detached from it. The regional climate of the area was determined from data collected from a nearby government operated meteorological station. Climatic inputs occurring on or near the moraine surface, from June 1 to July 25, 1972, were obtained from two micro meteorological stations located directly on its surface. All data was abstracted and shown on graphs as mean daily values. The number of days that one station exceeded the other either/or on a mean daily basis and over three hour intervals, was also noted over the study period.
Keywords: Geology.